2016
DOI: 10.3748/wjg.v22.i40.9028
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of adenocarcinoma occurring in sporadic fundic gland polyps observed by magnifying endoscopy with narrow band imaging

Abstract: Gastric fundic gland polyps (FGPs) are common non-adenomatous gastric polyps arising from normal fundic mucosa without Helicobacter pylori (H. pylori) infection. Although systemic FGPs associated with familial adenomatous polyposis (FAP) often have dysplasia, there are few reports of dysplasia occurring in sporadic FGPs, especially when detected by magnifying endoscopy with narrow band imaging (ME-NBI). We experienced two cases of adenocarcinoma occurring in sporadic FGPs, and their ME-NBI findings were very u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…8 A recent series reported red and semi-pedunculated gastric adenocarcinomas arising in normal mucosa. 9,10 In this patient, the color and shape of the malignancy seen with white light imaging were similar to those seen in hyperplastic polyps in H. pylori-positive mucosa. However, LCI showed endoscopic findings consistent with a malignant lesion and a background different from hyperplastic polyps.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…8 A recent series reported red and semi-pedunculated gastric adenocarcinomas arising in normal mucosa. 9,10 In this patient, the color and shape of the malignancy seen with white light imaging were similar to those seen in hyperplastic polyps in H. pylori-positive mucosa. However, LCI showed endoscopic findings consistent with a malignant lesion and a background different from hyperplastic polyps.…”
supporting
confidence: 60%
“…These findings of surface pattern have been observed in several patients with similar malignant lesions and play an essential role in distin-guishing this type of cancer from a benign polyp. 9,10 We reported that early gastric cancers show orange-red, orange-white, and purple colors using LCI. 3 It is noted that red cancers imaged with white light imaging change to purple with LCI.…”
mentioning
confidence: 99%
“…Gastric fundic gland polyp (FGP)-associated dysplasia/adenocarcinoma could be one of the differential diagnoses, because the neoplastic epithelium shows foveolar differentiation in our cases as well as in fundic gland polyps 17 20 . Gastric FGP reportedly rarely accompanies gastric cancer and has endoscopic and histologic findings quite similar to those in our cases 20 . However, as shown in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…HGD was equivalent to category 4 according to the Vienna classification, and classified as noninvasive intramucosal carcinoma according to the JCGC . Although there have been a few case reports of FGP with HGD/ intramucosal adenocarcinoma, deeper invasive adenocarcinoma arising in FGP has never been reported.…”
Section: Discussionmentioning
confidence: 99%